1, 3-Butadiene, styrene and lymphohaematopoietic cancers among North American synthetic rubber polymer workers: exposure–response analyses. (9th June 2021) - Sathiakumar, Nalini; Bolaji, Bolanle E; Brill, Ilene; Chen, Ligong; Tipre, Meghan; Leader, Mark; Arora, Tarun; Delzell, Elizabeth
Abstract : Objective: To evaluate exposure–response between 1, 3-butadiene, styrene and lymphohaematopoietic cancers in an updated cohort of workers at six North American plants that made synthetic rubber polymers. Methods: Employees were followed from 1943 through 2009 to determine mortality outcomes. Cox regression analyses estimated rate ratios (RRs) and 95% CIs by quartile of cumulative exposure to butadiene or styrene, measured in parts per million-years (ppm-years), and exposure–response trends for all leukaemia, lymphoid leukaemia, myeloid leukaemia, acute myeloid leukaemia, non-Hodgkin's lymphoma (NHL), multiple myeloma and all B-cell malignancies. Results: Among 21 087 workers, adjusted RRs for butadiene and all leukaemia (132 deaths) rose with increasing exposure, with an RR of 2.53 (95% CI 1.37 to 4.67) in the highest exposure quartile (≥363.64 ppm-years), and the exposure–response trend was statistically significant for all leukaemia (p=0.014) and for lymphoid leukaemia (52 deaths, p=0.007). Styrene exposure–response trends for all leukaemia and lymphoid leukaemia were less consistent than those for butadiene. Cumulative exposures to butadiene and styrene were not associated consistently with myeloid leukaemias or the B-cell malignancies, NHL and multiple myeloma. Conclusions: We confirmed a positive exposure–response relationship between butadiene and all leukaemia among workers, most of whom had coexposure to styrene. Results supported an association between butadiene and lymphoid leukaemia, but not myeloid leukaemia, and provided little evidence of any association of butadiene or styrene exposures with major subtypes of B-cell malignancies other than lymphoid leukaemia, including NHL and multiple myeloma.